Lamin-B1 contributes to the proper timing of epicardial cell migration and function during embryonic heart development - Tran, Joseph R. (Mol Biol Cell, 2016)
Lamin proteins form a meshwork beneath the nuclear envelope and contribute to many different cellular processes. Mutations in lamins cause defective organogenesis in mouse models and human diseases that affect adipose tissue, brain, skeletal muscle, and the heart. In vitro cell culture studies have shown that lamins help maintain nuclear shape and facilitate cell migration. However, whether these defects contribute to improper tissue building in vivo requires further clarification. By studying the heart epicardium during embryogenesis, we show that Lb1-null epicardial cells exhibit in vivo and in vitro migratory delay. Transcriptome analyses of these cells suggest that Lb1 influences the expression of cell adhesion genes, which could affect cell migration during epicardium development. These epicardial defects are consistent with incomplete development of both vascular smooth muscle and compact myocardium at later developmental stages in Lb1-null embryos. Further, we found that Lb1-null epicardial cells have a delayed nuclear morphology change in vivo, suggesting that Lb1 facilitates morphological changes associated with migration. These findings suggest that Lb1 contributes to nuclear shape maintenance and migration of epicardial cells and highlights the use of these cells for in vitro and in vivo study of these classic cell biological phenomena.